2019
DOI: 10.1186/s40673-019-0107-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cognitive profiles in spinocerebellar ataxia subtypes: a case series

Abstract: Background The spinocerebellar ataxias (SCA) are a heterogeneous group of progressive neurodegenerative disorders that are associated with diffuse cerebellar atrophy. While the physical symptoms of this condition have long been studied, more attention has been given to cognitive changes in recent years. We describe a case series of four adults with various genetically-confirmed subtypes of SCA. Case presentation Patients with SCA typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…More especially, their cognitive speed was reduced in two versions of a verbal naming task and their word fluency decreased compared to controls. These findings are in line with previous research reporting impaired processing speed and fluency in SCA2 patients 29 , in SCA3 patients 26 , and in both genotypes 6,25 . In a follow-up study, Moriarty and collaborators 8 reported more important difficulties in SCA3 compared to SCA2 patients.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…More especially, their cognitive speed was reduced in two versions of a verbal naming task and their word fluency decreased compared to controls. These findings are in line with previous research reporting impaired processing speed and fluency in SCA2 patients 29 , in SCA3 patients 26 , and in both genotypes 6,25 . In a follow-up study, Moriarty and collaborators 8 reported more important difficulties in SCA3 compared to SCA2 patients.…”
Section: Discussionsupporting
confidence: 93%
“…Some studies have described these abilities more extensively in specific genotypes. A case study observed slowed processing speed and reduced mental flexibility in SCA2, 3 and 6 patients 25 . Significant deficits in executive function processing speed and letter fluency were described in SCA3 patients, and letter fluency was shown to be correlated with functional neuroimaging measures 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Spinocerebellar Ataxia Type 2 (SCA2) is characterized by a cerebellar syndrome associated with slow saccades, early hyporeflexia, severe postural tremor, peripheral neuropathy, cognitive impairments, and other multisystem features [7]. In this sense, the scientific literature consulted supports the presence of cognitive alterations in SCA2 [2,4,15,20,27]. However, despite being one of the most frequent forms of hereditary ataxias, its approach from the field of study of Neuropsychology is insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…Spinocerebellar ataxia type 14 (SCA14) [OMIM: 605361] ( Yamashita et al, 2000 ; Brkanac et al, 2002 ) ( Rossi et al, 2014 ) is an autosomal dominant disorder characterized by progressive cerebellar degeneration, dysarthria, and nystagmus. Symptoms, such as axial myoclonus ( Yamashita et al, 2000 ), cognitive impairment ( Wedding et al, 2013 ; Bolton and Lacy, 2019 ), tremors ( Koht et al, 2012 ), and impaired sensibility ( Klebe et al, 2005 ; Koht et al, 2012 ), may also be observed. Furthermore, Parkinson’s disease ( Sailer et al, 2012 ; Chen et al, 2022 ), which is characterized by muscle rigidity and tremors, has also been reported in some family pedigrees.…”
Section: Introductionmentioning
confidence: 99%